Cardiovascular, Respiratory, and Functional Effects of Home-Based Exercise Training after COVID-19 Hospitalization - Teixeira Do Amaral, Vanessa [UNESP]; Viana, Ariane Aparecida [UNESP]; Heubel, Alessandro Domingues; Linares, Stephanie Nogueira; Martinelli, Bruno; Witzler, Pedro Henrique Camprigher [UNESP]; Orikassa De Oliveira, Gustavo Yudi [UNESP]; Zanini, Gabriel De Souza [UNESP]; Borghi Silva, Audrey; Mendes, Renata Goncąlves; Ciolac, Emmanuel Gomes [UNESP] (Wolters Kluwer, 2022)
Introduction The present randomized, single-center, and single-blinded clinical trial tested the hypothesis that tele-supervised home-based exercise training (exercise) is an effective strategy for improving cardiovascular, respiratory, and functional capacity parameters in individuals who were hospitalized due to coronavirus disease 2019 (COVID-19). Methods Thirty-two individuals (52 ± 10 yr; 17 were female) randomly assigned to exercise (n = 12) or control groups (n = 20) had their anthropometric (weight, body mass index), hemodynamic (brachial and central blood pressure), vascular (arterial stiffness), ventilatory (pulmonary function and respiratory muscle strength), and functional parameters (handgrip strength, five-time sit to stand, timed up and go test, and 6-min walking test) assessed at baseline (30-45 d of hospital discharged) and after 12 wk of follow-up. Results Both groups similarly increased (P < 0.001) forced vital capacity (absolute and percent of predicted), forced expiratory volume in the first second (absolute and percent of predicted), and handgrip strength during follow-up. However, only the exercise group reduced carotid-femoral pulse wave velocity (-2.0 ± 0.6 m·s-1, P = 0.048) and increased (P < 0.05) resting oxygen saturation (1.9% ± 0.6%), mean inspiratory pressure (24.7 ± 7.1 cm H2O), mean expiratory pressure (20.3 ± 5.8 cm H2O), and percent of predicted mean expiratory pressure (14% ± 22%) during follow-up. No significant changes were found in any other variable during follow-up. Conclusions Present findings suggest that tele-supervised home-based exercise training can be a potential adjunct therapeutic to rehabilitate individuals who were hospitalized due to COVID-19.
Keywords: Arterial Stiffness; Pulmonary Function; Remote Home-Based Exercise; SARS-COV-2; Telerehabilitation